RELATIONS BETWEEN PLANNING AND POWER - Balestrieri, Mara (European Scientific Journal, ESJ, 2014)
What is the relationship between planning and power? What kind of impact does it have on planning processes and governance of space? What kind of coercion should be exerted to regulate the built environment? Only recently has theoretical reflection on planning explicitly and directly addressed the question of the power planning necessarily possesses, trying to grasp the difference between physiological situations and pathological conditions, where there is a distortion of the relationship with decision-making, and other, power in implementing technical action. But this has not clarified the relationship properly. The paper addresses the issue by reflecting on some interpretative categories of power, their transposition onto the territorial urban dimension and their effects in terms of planning, so as to obtain the recognition of power as an important key to understanding spatial and functional organisation and to highlight how the link between planning and power often does not produce effects of collective safeguarding but of the defence of a few to the detriment of many.